The anharmonicity role of interatomic potential in predicting glass formation. (15th July 2022) - Yu, Jinhua; Wang, Zheng; Hu, Lina; Chu, Wei; Bai, Yanwen
Abstract: Although many criteria were proposed to predict the glass forming ability (GFA) of alloys, the precise correlation between the minor addition of elements and the glass formation remains a challenge. To solve this problem, we propose a simple parameter α' derived from thermal expansion coefficient based on the details of the intrinsic interatomic potential. It has been found that α' has the capability of precisely predict the changes of GFA, indicating the important role of anharmonicity of atomic vibration in glass formation. This anharmonicity-related parameter α' relates to atomic mobility behavior, and could be well embodied by the competition between characteristic types of clusters in terms of the fragility concept upon the liquid-solid evolution. This work not only helps to uncover atomic and cluster origins of glass formation from interatomic potential, but also provides a novel route to precisely evaluate the effect of minor addition of elements on GFA. Graphical abstract: Image, graphical abstract